Immigrant workers and farm performance: Evidence from matched employer-employee data - Nikolaj Malchow-Møller; Jakob Roland Munch; Claus Aastrup Seidelin; Jan Rose Skaksen (Institute for the Study of Labor (IZA), 2013)
Many developed countries have recently experienced a significant inflow of immigrants in the agricultural sector. At the same time, the sector is still in a process of structural transformation resulting in fewer but bigger and presumably more efficient farms. In this paper, we exploit detailed matched employer-employee data for the entire population of Danish farms in the period 1980-2008 to analyze the micro-level relationship between these two developments. We find that farms that employ immigrants tend to be both larger and at least as productive as other farms. Furthermore, an increased use of immigrants is found to be associated with an improvement in farm performance as measured by job creation and revenue, and this seems at least in part to reflect a causal effect of the immigrants.
Keywords: J61; J43; 330; immigration; agriculture; matched employer-employee data; Landwirtschaft; Unternehmenserfolg; Ausländische Arbeitskräfte; Betriebsgröße; Dänemark